FULLFILMENT: SEBUAH TINJAUAN HISTORIKAL-TEOLOGIS - Made Nopen Supriadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2017)
The study of eschatology is inseparable from the concept of fulfillment. What will be fulfilled at the end of time? Then who is the person who will fulfill everything at the end of time? Therefore, to give an understanding to believers about the teaching of fullfilment, this paper will explore Biblically and formulate systematically by looking at the views of the theologians who wrote the topic.